The Influence of Intellectual Capital, Good Corporate Governance, Funding Decisions and Investment Decisions on Firm Value Mediated by Profitability as an Intervening Variable in LQ45 Companies for the 2020–2024 Period - Adhan, Ahmad; Suryani, Arna; Akbar, Ali (DINASTI RESEARCH, 2025)
This study aims to analyze the influence of intellectual capital, good corporate governance, funding decisions, and investment decisions on firm value, with profitability as an intervening variable, in LQ45 companies during the 2020–2024 period. The sampling method used in this research is purposive sampling, in which 26 companies listed in the LQ45 index were selected as the research sample. The secondary data were obtained from annual financial reports. The results of this study indicate that intellectual capital has a significant effect on profitability; good corporate governance has a significant effect on profitability; funding decisions have a significant effect on profitability; investment decisions have a significant effect on profitability; intellectual capital has a significant effect on firm value; good corporate governance has a significant effect on firm value; funding decisions have a significant effect on firm value; investment decisions have a significant effect on firm value; profitability does not have a significant effect on firm value; intellectual capital through profitability does not have a significant effect on firm value; good corporate governance through profitability does not have a significant effect on firm value; funding decisions through profitability have a significant effect on firm value; and investment decisions through profitability have a significant effect on firm value.